Risk factors for the development of depression in patients with hepatitis C taking interferon-α - Smith KJ (Dove Medical Press, 2011)
Kimberley J Smith¹, Suzanne Norris², Cliona O'Farrelly³, O'Mara SM¹¹Trinity College Institute of Neuroscience, ²Hepatology Centre, St James's Hospital, Dublin, Ireland; ³Department of Biochemistry and Immunology, Trinity College Dublin, Dublin, IrelandAbstract: Interferon-α, currently used for the treatment of hepatitis C, is associated with a substantially elevated risk of depression. However, not everyone who takes this drug becomes depressed, so it is important to understand what particular factors may make some individuals more 'at risk' of developing depression than others. Currently there is no consensus as to why interferon-induced depression occurs and the range of putative risk factors is wide and diverse. The identification of risk factors prior to treatment may allow identification of patients who will become depressed on interferon, allowing the possibility of improved treatment support and rates of treatment adherence. Here, we consolidate and review the literature on risk factors, and we discuss the potential confounds within the research examined in order to better isolate the risk factors that may be important in the development of depression in these patients and which might help predict patients likely to become depressed on treatment. We suggest that interactions between psychobehavioral, genetic, and biological risk factors are of particular importance in the occurrence of depression in patients with hepatitis C taking interferon-α.Keywords: interferon-α, risk factors, depression, hepatitis C